Martensopsalis, a new genus of Neopilionidae from New Caledonia (Opiliones: Eupnoi) - Giribet, Gonzalo; Baker, Caitlin M.; Brouste, Damien (Zootaxa, 2021)
New Caledonia has an endemic opiliofauna with two named species of Triaenonychidae, 17 Troglosironidae and eight Zalmoxidae. The recent finding of Neopilionidae on Grande Terre was thus surprising, and required the formal description of a new genus, which we undertake here. Martensopsalis gen. nov. is characterized by a small unsclerotized body with a unique palp with a pointed basal apophysis on the ventral side of the femur and with a distal apophysis on the prolateral side of the patella. The distinct external morphology, simple penis and unique phylogenetic position justify the erection of the new genus with Martensopsalis dogny spec. nov. as its type species. In addition to the type locality we report several other localities of putative congeneric, yet undescribed species.